Perawatan Metode Kanguru terhadap Kenaikan Berat Badan Bayi - Windi Nur Emiria; Yeni Rustina; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2023)
This study aims to provide an overview and ideas from published research results regarding the effectiveness of the kangaroo treatment for weight gain in LBW. The method used is a systematic review using a search strategy on eight electronic databases: Taylor & Francis Online, ProQuest, Semantic Scholar, Scopus, Science Direct, PubMed, EBSCOhost, and Google Scholar. The keywords used in the search were (premature OR "low birth weight infant") AND ("kangaroo mother care" OR "kangaroo care") AND ("weight gain" OR growth OR "infant weight gain"). The results showed that most kangaroo treatments are intermittent PMK, namely PMK given at any time, usually when parents visit their babies. The duration of PMK implementation varies between 30 minutes in one day to 20 hours in one day. In conclusion, the kangaroo method treatment is proven to be effective in increasing the baby's weight compared to conventional treatments that are usually done. Keywords: LBW, Infant Weight Gain, Kangaroo Method Care